An improvement of spatial data quality assessment process on geographical information system - Arris, Artiesa (2017)
The use of Geographical Information Systems has flooded almost every field in the engineering, natural and social sciences, offering accurate, efficient, reproducible methods for collecting, viewing and analyzing spatial data. GIS data have become a progressively essential data type to Malaysian Government Agencies and to business in general. An effective GIS data and information is needed to reduce losses from natural & human-induced disaster as prevention and early warning. Spatial data is one of important GIS element where contain Information about the locations and shapes of geographic features and the relationships between them, usually stored as coordinates and topology. Meanwhile, Spatial Data quality is the degree of data that fulfill the given objective. In other words, completeness of attributes in order to achieve the given task can be termed as Data Quality. Production of data by government agencies as well as by various mapping agencies assesses the data quality standards in order to produce better results. Data created from different channels with different techniques may have a conflict in terms of resolution, orientation and displacement. Spatial Data quality is a pillar in any GIS implementation and application as reliable data are indispensable to allow the user obtaining meaningful results. As a result, study on spatial data quality assessment guideline published by MaCGDI is important to DID and relevant to benchmark. Spatial Data Quality Assessment process flow has been designed in order to improve the existing procedure.